2010
DOI: 10.1159/000320193
|View full text |Cite
|
Sign up to set email alerts
|

β<sub>2</sub>-Microglobulin, Pulse Pressure and Metabolic Alterations in Hemodialysis Patients

Abstract: Background/Aim: Pulse pressure (PP) is a result of arterial stiffness seen in dialysis patients, but may be a consequence of fluid overload. We examined the role of β2-microglobulin (β2M) in PP in relation to metabolic alterations in patients on different hemodialysis (HD) modalities. Methods: We studied 76 hemodialyzed patients on regular HD (n = 34), predilution bagged hemodiafiltration (n = 19) and online predilution hemodiafiltration (n = 23). β2M levels were measured by ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 85 publications
2
11
1
Order By: Relevance
“…Our results showed an increase in aortic PWV in patients who remained on haemodialysis or were only recently transferred to haemodiafiltration, whereas there was no overall increase for those established on haemodiafiltration, and are supported by two earlier smaller single-centre studies: one reporting that patients dialysing with haemodiafiltration had lower PWV measurements than those treated by conventional haemodialysis [20] and another noting increased PWV in haemodialysis patients, but with no increase with haemodiafiltration [21]. Although another study observed no differences in carotid-femoral PWV between haemodialysis and haemodiafiltration groups [22], this negative study of just over 100 patients employed multiple observers making a limited number of measurements in a younger dialysis population with fewer diabetics with no correction for heart rate.…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed an increase in aortic PWV in patients who remained on haemodialysis or were only recently transferred to haemodiafiltration, whereas there was no overall increase for those established on haemodiafiltration, and are supported by two earlier smaller single-centre studies: one reporting that patients dialysing with haemodiafiltration had lower PWV measurements than those treated by conventional haemodialysis [20] and another noting increased PWV in haemodialysis patients, but with no increase with haemodiafiltration [21]. Although another study observed no differences in carotid-femoral PWV between haemodialysis and haemodiafiltration groups [22], this negative study of just over 100 patients employed multiple observers making a limited number of measurements in a younger dialysis population with fewer diabetics with no correction for heart rate.…”
Section: Discussionsupporting
confidence: 83%
“…It is well known that both muscle wasting and arterial stiffness are prevalent in CKD. Previous studies have shown that PTH, vitamin D, and acidosis are associated with arterial stiffness, as well [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a faster decline in RRF is noticed in thrice weekly conventional HD compared with PD, which is attributable to common intradialytic hypotension and abrupt volume depletion in HD [7]. However, the use of on-line hemodiafiltration (HDF) with high-flux biocompatible membranes and ultrapure water for dialysate may preserve RRF longer, due partly to less sodium removal compared with conventional HD, resulting in less intradialytic hypotension and improved intradialytic cardiovascular stability [8,9].…”
mentioning
confidence: 99%